Research on multi-objective optimal allocation of regional water resources based on improved sparrow search algorithm - Yao, Zhiyuan; Wang, Zhaocai; Cui, Xuefei; Zhao, Haifeng (Journal of hydroinformatics, 2023)
Nowadays, the conflict between the supply and demand of water resources in many regions is becoming increasingly prominent. Scientific allocation of regional water resources has become the key to solving the contradiction. In this study, a regional multi-objective water resources optimization allocation model considering social, economic, and ecological objectives is established, and four improvement spots are introduced to the sparrow search algorithm (SSA) to form an improved sparrow search algorithm (ISSA). By testing nine benchmark functions including monotonic and multi-peaked, the search efficiency and average convergence results of ISSA are significantly enhanced compared with other intelligent algorithms. Meanwhile, this research uses Luanchuan County, Henan Province, China, as an example to solve the water resource allocation scheme for 2025 and 2030 in the region using ISSA. The results show that the overall water shortage rate decreases to 3.49 and 2.79%, respectively, under the 75% guarantee rate, resulting in an effective reduction in future water shortages. Simultaneously, the scheme proposed has sound comprehensive benefits and can provide important technical support for the refined management of water resources, which is a reference and guidance for solving the contradiction between water supply and demand at the current stage.